Pengaruh Debt to Equity Ratio (DER) dan Return on Equity (ROE) terhadap Harga Saham pada PT Bank Syariah Indonesia Tbk - Astrina Fitriani; Mulia Inda Purwati; Kiki Helencia (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to determine and analyze the effect of Debt to Equity Ratio (DER) and Return on Equity (ROE) on stock prices at PT Bank Syariah Indonesia Tbk for the period 2021–2024. This study used a quantitative approach with an associative research type. The data used were secondary data obtained from the annual financial statements of PT Bank Syariah Indonesia Tbk for the period 2021–2024. The sampling technique used purposive sampling, with samples in the form of company financial statements containing DER, ROE, and stock price data. The data analysis techniques used included descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) using the SPSS program. The results of the study indicate that partially Debt to Equity Ratio (DER) and Return on Equity (ROE) partially have a significant effect on stock prices. Simultaneously, Debt to Equity Ratio (DER) and Return on Equity (ROE) have a significant effect on stock prices with a significance value of 0.000 <0.05. The coefficient of determination (R Square) value of 0.487 indicates that DER and ROE are able to explain the effect on stock prices by 48.7%, while the remaining 51.3% is influenced by other variables outside the study.